Scroll, watch, engage? A data-driven content analysis of celebrity physicians’ health video strategies on Douyin - Zhang, Xin; Kamarudin, Syafila; Tang, Qing Qing; Liu, Xuan Tai (Emerald Publishing, 2025)
Purpose: While short-video platforms have gained prominence in health communication, limited research has investigated their role in physician-led health messaging. The objective of this study is to enhance understanding of how celebrity physicians in China use Douyin for health communication and audience engagement. Design/methodology/approach: A quantitative content analysis was conducted on 240 videos from 30 celebrity physicians, collected between 6 November and 6 December 2023. A coding framework comprising 4 main categories and 41 subcategories was developed based on message sensation value theory to assess account engagement, video content, video format and health-care promotion. The coding process was completed in January 2024. Findings: User engagement largely remained at the level of likes and saves, with fewer deeper interactions such as comments and shares. Results also indicate viewers strongly preferred health advice content featuring concise oral narration by a single physician, short video duration, original background music and clear subtitles. Educational and humorous presentations significantly boosted user engagement. However, ethical concerns emerged, notably regarding information accuracy and transparency in advertisements, potentially influencing audience trust toward celebrity physician-led content. Originality/value: The findings contribute to the growing body of literature on digital health communication and offer practical recommendations for both celebrity and non-celebrity physicians to enhance their health messaging strategies on Douyin and similar platforms.